PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS E-MODUL TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM SARAF KELAS XI DI SMA N 18 MEDAN - Kemini Deliana Lumban Gaol; Masdiana Sinambela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning outcomes refer to the skills acquired by students after undergoing a series of instructional experiences provided by educators. These experiences comprehensively integrate the cognitive, affective, and psychomotor domains. Conceptually, learning outcomes represent the capabilities an individual gains through learning processes within an educational institution, as evidenced by learning evaluations. This study aimed to determine the differences in student learning outcomes when comparing an e-module based Problem-Based Learning (PBL) model with a direct instruction model regarding the topic of the nervous system. A quantitative approach utilizing a quasi-experimental design was employed. Simple random sampling was used to select the sample, while data were collected via tests and analyzed using N-gain and t-tests at a significance level of 0.05. The analysis revealed a difference in learning outcomes between the class using the PBL model and the class using the direct instruction model. Specifically, the average scores were 0.6888 or 68.88 for the PBL class and 0.1563 or 15.63 for the direct instruction class. Thus, the PBL model proved superior to direct instruction in enhancing learning outcomes. Based on the results and discussion, it is concluded that there is a difference in learning outcomes between the e-module based PBL model and the direct instruction model regarding the nervous system topic.